The mechanisms of glycolipid metabolism disorder on vascular injury in type 2 diabetes - Chen, Xiatian; Shi, Chengzhen; Wang, Yin; Yu, Hua; Zhang, Yu; Zhang, Jiaxuan; Li, Peifeng; Gao, Jinning (Frontiers in Physiology, 2022)
Patients with diabetes have severe vascular complications, such as diabetic nephropathy, diabetic retinopathy, cardiovascular disease and neuropathy. Devastating vascular complications lead to increased mortality, blindness, kidney failure and a decrease in overall quality of life in people with type 2 diabetes (T2D). Glycolipid metabolism disorder plays a vital role in T2D vascular complications. However, the specific mechanism of action remains to be explored. In T2D patients, vascular damage begins to develop before insulin resistance and clinical diagnosis. Endothelial dysregulation is a significant cause of vascular complications and the early event of vascular injury. Hyperglycemia and hyperlipidemia can trigger inflammation and oxidative stress, which impair endothelial function. Furthermore, during the pathogenesis of T2D, epigenetic modifications are aberrant and activate a variety of biological processes, resulting in endothelial dysregulation. In the present review, we overviewed and discussed the role of endothelial dysfunction, inflammatory response, oxidative stress and epigenetic modification in the pathogenesis of T2D, which is induced by hyperglycemia and hyperlipidemia. Understanding the connections between glucotoxicity and lipotoxicity, and vascular injury may reveal a novel potential therapeutic target for diabetic vascular complications.